ECONOMIC STUDY OF OBTEINING LIGNOCELLULOSIC BIOETHANOL (Journal of Industrial and Mechanical Engineering, 2019)
According studies achieved, Argentina has areas with a potential surplus of energy biomass, it has suitable conditions for the development of the basic inputs which are necessary for the production of energy frombiomass; also, it has great potential and comparative advantages for the production of biofuels.The aim of this work is to analyse the economic viability of obtaining lignocellulosic bioethanol, through corn stubble. The analysis has addressed the economic convenience convert corn stubble into bioethanol, applying the criterion of forming productive complexes.The obtained results have demonstrated the existence of gross profit for the members of the productive complex, and they are considered as a valuable approximation to the production of bioethanol.The methodology used for the analysis was based on the Monte Carlo simulation method.The conclusions reached are orientated to the economic side without taking into account the analysis of the productive process and an initial investment.
Keywords: biofuels; lignocellulosic bioethano; monte carlo simulation; economic viability